Ecological Notes on the Vegetation of Coorg District, Western Ghats - Arora, R. K. (Indian Forester, 1965)
The floristic composition of three Forest types, i.e., scrub, deciduous and evergreen forests, for the district of Coorg is described, and the status of each type has been indicated. The interrelationship of these three types is presented and the status of the climax types discussed. The different communities as worked out for each Forest type have been rated on comparative basis.